(untitled) (Fiep Bulletin - online, 2014)
The football is one of the most culture expressions in Brazilian society. Through this we created, we transmit and we strengthen the culture value and believe. In this way, the football field has to be seen as symbolic field full of cultures means that vary as society and culture that they are inserted. This make people represent, feeling, and read the football in a different way in each region, and is notable the changes of mean even though between an urban region and a country region. In the societies exist, mediations places between country logics and urban logics. Sport and the leisure "social spaces" tend to possibility the interactions. In this way, this work object was analyze a leisure space in a city called Viçosa, in the Zona da Mata, Was saw the way is transmit, create and it allows the culture values interaction social, even in country or urban region. For this way, has realized a work with three practitioners groups, during four months. Was perceive that football has a meaning for this locate, mainly, in the interaction between two "ethics", country and urban.